Model Matematika Penyebaran Penyakit Toksoplasmosis - Resti Indrawati Utami; Riry Sriningsih (UNIVERSITAS NEGERI PADANG, 2018)
Abstract– Toxoplasmosis is a disease that affected by Toxoplasma gondii parasite which have latent (asymptomatic) characteristic. Toxoplasmosis disease was spreading vertically and horizontally. Spreading vertically through mother to kids and spreading horizontally through uncooked that contain of ookista. Toxoplasmosis disease can affect to serious health problems including physical disability, miscarriage and death. To determine influence level of Toxoplasmosis disease spreading, mathematic model was divided population by four individual groups: susceptible individual, latent individual, infection individual and controlled individual. Mathematical model formed was analysed by looking at its stability, analysis result was obtained fixed stability point. Increase in sum of individuals Toxoplasmosis disease spreading was affected by three parameters, which were susceptible individual moving to latent individual due to consume the foods that contain of ookista, individual that infected due to decrease immune system, and controlled individual or given treatment.